(untitled) (Research, Society and Development, 2021)
Currently, Brazil is an agricultural power, being the largest producer of soy with the use of innovation and cutting-edge technology, it even managed to surpass the United States in the last harvest. The Northern region of Brazil is not a traditional region in soy production, therefore the State of Pará is not either. However, a phenomenon has been taking place. Little by little, the rural area, which has always had dairy and beef cattle raising, is losing space to soy plantations. There are several possible impacts that the arrival of soy farms has brought to the local community of Rondon do Pará, generating positive and negative criticism. Thus, this work aims to map and discuss which actors were most impacted by the transformations brought by soy farms to the city of Rondon do Pará-PA. The methodology adopted to carry out the research was qualitative, with triangulation of data in the collection, using participant observation, document analysis and semi-structured interviews. It is concluded, among other things, that soy producers had a direct impact on the concentration of land ownership and income. Public authorities now have an even more important role, to mediate and create public policies that make inequality possible. Direct labor, less educated, had less impact, however a considerable number of suppliers were developed in the city to meet the demand for soy.